Peran Penyuluh Terhadap Kualitas Susu Yang Dihasilkan Peternak Sapi Perah Ditinjau Dari Kadar Lemak Dan Berat Jenis Susu Di Kabupaten Wonosobo - Wibowo, Muhammad Adi; Muatip, Krismiwati; Soediarto, Pramono (ANGON: Journal of Animal Science and Technology, 2019)
Background.The aim of the study was to determine the quality of milk produced by dairy farmers in Wonosobo Regency in terms of fat content and specific gravity, to know the role of extension agents so that dairy farmers produce quality dairy cows and analyze the relationship between the role of extension agents and milk quality produced by dairy farmers in terms of fat content and specific gravity. Materials and methodsThe research target is dairy farmers in Wonosobo Regency. Sampling of the area was carried out by purposive sampling, namely sub-districts that have a dairy cattle population in Wonososbo Regency. Census respondents took the research in selected regions, with 32 respondents as dairy farmers. Results. The analysis used is descriptive analysis and Rank Spearman analysis. Milk quality test results in the form of fat content and specific gravity of milk in Wonosobo District showed positive results, namely the average fat content above 2.9% and specific gravity above 1.0269 g/ml. The role of livestock extension agents in Wonosobo Regency has been good enough at helping dairy farmers to produce quality milk according to SNI standards. Conclusion. The Rank Spearman correlation analysis showed that there was a very significant relationship between the role of extension agents and the level of milk fat produced by farmers with a correlation coefficient of 0.525 and there was no relationship between the role of extension agents and milk quality seen from milk specific gravity with a correlation coefficient of 0.336.